Pendapatan Asli Daerah, Penanaman Modal dalam Negeri, dan Inflasi Terhadap Produk Domestik Bruto di Indonesia 2019-2020 - Elsa Agustin Prasetyawati; Wikan Budi; Maya Widyana (Nur Science Institute, 2026)
This research is a type of quantitative research which aims to determine the influence of local revenue, domestic investment, inflation on Indonesia's gross domestic product in 2019-2020. The type of data used in this research is secondary data which comes from the Budget Realization Report and statistical data reports from the Indonesian Central Statistics Agency in 2019-2020. The sampling technique in this research used a saturated sampling technique. The number of samples in this research was 68 samples. The data analysis method used is the classical assumption test and multiple linear regression test, F test, t test, R2 test. The results of the t test produce a significance value of local original income of 0.000, domestic investment of 0.170, inflation of 0.394. The results of the t test, the PAD variable produces a significance value below 0.05, namely 0.000, so the PAD variable has a significant effect on GDP. The PMDN variable produces a significance value above 0.05, namely 0.170, so the PMDN variable does not have a significant effect on GDP. The inflation variable produces a significance value above 0.05, namely 0.394, so the inflation variable does not have a significant effect on GDP.